Gender differences in bilateral and ipsilateral lower limb strength asymmetry among football players - Randy R. Manimtim; Eissel Ronquillo (Sport, Exercise, and Injury, 2026)
Background: Lower limb muscle strength asymmetry is a significant factor that can impact playing ability and increase the risk of injury in soccer players. Differences in leg use and the specific movement requirements of a sport can lead to strength imbalances, either on both sides of the body or on the same side. Lower limb muscle strength asymmetry, particularly bilateral and ipsilateral strength asymmetry, is a significant factor influencing performance and increasing injury risk in football players. Differences in limb dominance and sport-specific movement demands can lead to strength imbalances. Objectives: This study aimed to compare bilateral and ipsilateral lower limb strength asymmetry between male and female football players. Methods: A cross-sectional study was conducted involving 50 amateur football players (26 males and 24 females; aged 18–21 years). Isokinetic strength testing of knee extensors and flexors was performed at 60°/s. Bilateral asymmetry was calculated based on peak torque differences between limbs, while ipsilateral asymmetry was assessed using the hamstring-to-quadriceps (H/Q) ratio. Statistical analyses included the Mann–Whitney U test and independent t-test (p < 0.05). Results: Significant sex differences were found in bilateral strength asymmetry for both quadriceps (7.21 ± 4.04% vs 5.04 ± 3.13%, p = 0.02) and hamstrings (9.13 ± 5.15% vs 5.06 ± 4.04%, p = 0.01), with males showing greater asymmetry. Female athletes demonstrated values closer to the recommended asymmetry threshold (≤10–15%). No significant differences were observed in ipsilateral strength asymmetry (H/Q ratio) between groups (p > 0.05). Conclusions: Bilateral strength asymmetry differs by sex, with male athletes exhibiting higher imbalance, while ipsilateral strength balance is comparable between groups. These findings highlight the importance of monitoring individual strength asymmetry to inform targeted training strategies, reduce injury risk, and optimize performance in football players.